PEMBELAJARAN RECIPROCAL TEACHING DAN METAKOGNITIF (RTM) YANG MEMBERDAYAKAN KETERAMPILAN METAKOGNITIF DAN HASIL BELAJAR BIOLOGI SISWA SMP - Zusje W. M. Warouw (Jurnal Ilmu Pendidikan, 2016)
Abstract: Reciprocal and Metacognitive Teaching Empowering Metacognitive Skills and Biology Learning Achievements of Junior High School Students. The study tries to reveal influence of the learning strategies toward metacognitive skills and biology learning; influence of academic capability toward metacognitive skills and learning; influence of academic capability and learning strategy interaction toward metacognitive skills and learning. Data was analyzed using ANCOVA. Results showed that strategy of RTM had significant influence in improving metacognitive skill of the students who had low and high academic capabilities. The study also found that the strategy would improve learning of the students who had high academic capabilities.